The Effect Of Understanding Tax Regulations, Moral Obligations And Financial Conditions On Hotel And Restaurant Taxpayer Compliance In Banyuwangi Regency - Pristiwantiyasih, Pristiwantiyasih (International Journal of Science, Technology & Management, 2023)
This study aims to determine the effect of understanding tax regulations, moral obligations and financial conditions on hotel and restaurant taxpayer compliance in Banyuwangi Regency. The sampling technique in this study used the simple random sampling method. The sample used in this study is hotel and restaurant taxpayers registered with the Banyuwangi Regency Revenue Agency. Collecting data in this study using a questionnaire method involving a sample of 89 hotel and restaurant taxpayers. Data analysis used quality test, classical assumption test, multiple linear regression test, hypothesis test and coefficient of determination test. Processing data in this study using SPSS 25. Based on the results of calculations obtained t test results indicate that the effect of understanding tax regulations, moral obligations and financial conditions affect taxpayer compliance. And the results of the study using the F test stated that the understanding of tax regulations, moral obligations and financial conditions had a simultaneous effect on taxpayer compliance.